Immunolocalization and proteomic analyses of IZUMO1 in porcine spermatozoa - Hernández-Falcó, Miranda; Sáez-Espinosa, Paula; López-Botella, Andrea; Robles-Gómez, Laura; García-Vázquez, Francisco Alberto; Izquierdo-Rico, Maria José; Llamas-López, Pedro José; Gómez-Torres, María José (Frontiers in Cell and Developmental Biology, 2025)
Reproduction is fundamental to breeding programs aimed at increasing productivity in swine industry. However, the application of in vitro embryo production in this species is limited because of the polyspermy. Therefore, characterizing proteins involved in sperm-oocyte binding such as IZUMO1 becomes essential. This study aimed to characterize porcine IZUMO1 protein under three different physiological states: sperm-rich fraction (SRF), 1-h capacitated sperm selected by swim-up (CS), and induced acrosome reaction in 1-h capacitated sperm (ARS). The immunolocalization of IZUMO1 and acrosome status of fifteen fertile boars was assessed by confocal microscopy. Additionally, six males were subjected to a more detailed examination via quantitative proteomic analysis by LC–MS/MS. Fluorescence results revealed four distinct IZUMO1 distribution patterns: pattern 1 (P1) characterized by speckled staining in the pre-equatorial subdomain and postacrosomal domain, pattern 2 (P2) displaying strong apical ridge staining with speckled staining in the pre-equatorial subdomain and postacrosomal domain, pattern 3 (P3) exhibiting speckled staining in the postacrosomal domain, and pattern 4 (P4) without labelling. In the SRF sperm, IZUMO1 was predominantly distributed between staining patterns P1 and P2 (∼50%). As a result of the capacitation, there was a significant decrease in P1. Conversely, in ARS, IZUMO1 was dominantly distributed in P3 51.55% and P4 24.25%. The quantitative study of the IZUMO1 protein supported these findings. With those results and compared with our previous work in human, here we propose a working model of IZUMO1 migration dependent on the morphology and subdomains of the sperm head.